A greener vision of home : cultural politics and environmental reform in the German Heimatschutz movement, 1904 - 1918 - Rollins, William H. (Social history, popular culture, and politics in Germany, 1997)
Suburban sprawl, advertising clutter, vast industrial plantations of spindly pines punctuated by stone-lined gutters in place of streams - this was the thoroughly modern landscape of Germany by the turn of the century. Most people ignored the devastating changes in their environment, or quickly rationalized them away as the price that had to be paid for "progress." But in 1904, three-quarters of a century before Greenpeace, one group arose that did not compromise on conservation: the movement for "homeland-protection," or Heimatschutz. Aesthetic or "romantic" ideas about the environment have often expressed valuable critiques of our all-too-utilitarian modern lifestyles. In the English-speaking world John Ruskin and William Morris are well known for this kind of ecological antimodernism; a very similar aesthetic concern for landscape energized the Heimatschutz movement. Drawing on a wide range of archival and printed sources, many made accessible here for the first time, William H. Rollins shows that this was a broad-based middle-class reform movement that combined social egalitarianism with protection for the entire working landscape. A Greener Vision of Home will appeal to readers in German studies and cultural studies and others interested in some of the roots and major strategies of today's highly visible environmental movement.